2021
DOI: 10.1144/geochem2019-082
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of rare earth elements (REEs) in soils developed on different parent materials, in the Baoshan area, Yunnan Province, SW China

Abstract: The geochemistry of rare earth elements (REEs) was studied in rock samples from host formations, ore samples from two mineral deposits (the Hetaoping Cu-Pb-Zn mine: HTP and the Heiyanao Fe-Cu-Pb-Zn mine: HYA) and the overlying or nearby soils to better understand REE concentrations, distributions and behaviour during weathering from different parent materials at the regional scale, Baoshan area, Yunnan Province, Southwest China. The mudstone and sandstone formations have highest total REE (ΣREE) contents. Chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…With the research into heavy metals pollution becoming the focus of attention, many scholars have carried out some related research about the content status, distribution characteristics, pollution levels and enrichment factors of heavy metals in the southwest karst landforms of China in recent years [ 13 , 14 , 15 , 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, there are few studies on the sources of agricultural heavy metals, which affects the scientific judgment about soil heavy metals pollution.…”
Section: Introductionmentioning
confidence: 99%
“…With the research into heavy metals pollution becoming the focus of attention, many scholars have carried out some related research about the content status, distribution characteristics, pollution levels and enrichment factors of heavy metals in the southwest karst landforms of China in recent years [ 13 , 14 , 15 , 16 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, there are few studies on the sources of agricultural heavy metals, which affects the scientific judgment about soil heavy metals pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The Baoshan area is located in Yunnan province, Southwest China (Figure 1a), has a low latitude and moderate elevation, and is tempered by a mild subtropical climate with short, mild, and dry winters and warm, wet summers. Variations in the average temperature are closely connected to altitude, while the western and southern parts of the study area experience the highest amount of rainfall [54,55,64]. The main land-use types in the study area are forested land, dry cultivated land, paddy land, grassland, and garden plots, with few water areas or other land types (residential quarters, industrial and mining land, and unused land) (Figure 1c) [54,55].…”
Section: Study Areamentioning
confidence: 93%
“…The PTE levels in soil are frequently elevated due to mineral resources (such as Cu, Pb, Zn, and Hg), as well as carbonate and basalt parent materials [56][57][58][59][60][61][62][63]. This phenomenon can be observed in the soils of the Baoshan area in Yunnan province, southwest China, where mineral resources and carbonate and basalt parent materials are widely distributed [54,55,64]. Previous study has shown the concentrations and the distribution of selected elements (including PTEs) in the soil and river sediments of the Baoshan area, based on the data from the 1: 250,000 scale National Geochemistry Survey of Land Quality project (NGSLQ) and archived river sediment samples collected and analyzed in the Regional Geochemistry-National Reconnaissance (RGNR) program based in this area (6220 km 2 ) [54].…”
Section: Introductionmentioning
confidence: 99%